Audio electronics - Hood, John Linsley; ScienceDirect eBooks (Oxford [England] ; Boston : Newnes, 1999)
This book is a unique electronics text in that it focuses on the electronics of audio design and explores the principles and techniques that underly the successful design and usage of analog and digital equipment. The second edition includes new material on the latest developments in the field: digital radio and television, Nicam 728, and the latest Dolby noise reduction systems. John Linsley Hood is responsible for numerous amplifier designs that have led the way to better sound, and has also kept up a commentary on developments in audio in magazines such as The Gramophone, Electronics in Action and Electronics World. Up-to-date material on the latest technological developments John Hood is a well-known and respected commentator on this industry.
Tape recording; Tuners and radio receivers; Preamplifiers and input signals; Voltage amplifiers and controls; Power output stages; The CD and digital audio; Test instruments and measurements; Loudspeaker crossover systems; Power supplies; Noise reduction; Digital audio for radio and television; Index.
Print version record.
Includes bibliographical references and index.
Safari Books Online
Elsevier
Keywords: Sound -- Recording and reproducing -- Equipment and supplies; Electronic circuits; TECHNOLOGY & ENGINEERING -- Electrical; Electronic circuits; Sound -- Recording and reproducing -- Equipment and supplies; Geluidsapparatuur; Elektronische schakelingen; Electronic books